Attitude of Mobile Assisted Pedagogy Approach in Teaching Science and Academic Achievement in Pedagogy Subject of Prospective Teachers - Prakash, N.R.; Devi, S. Nirmala (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Teaching of science is very challenging and more task oriented, there are several teaching approaches were available to teach the pedagogy subject such as constructivist approach, inquiry based teaching, reflective teaching approach, collaborative, integrative and techno-pedagogical approach. Hence, this present investigation aims to assess the attitude of mobile assisted pedagogy approach in teaching science and academic achievement in pedagogy subject of prospective teachers. The objective of the study is to find out the level of attitude of mobile assisted pedagogy approach in teaching science among prospective teachers and also to find out the significant difference between the subs samples such as gender, major subject, access of mobile application for learning and educational qualification. For the purpose of this study survey method was adopted and 171 B.Ed., teacher trainees from Chennai district of Tamil Nadu constituted sample for this present investigation. Sample selection was made using stratified random sampling technique. Collected samples were subjected to statistical analysis to form meaningful interpretation. The result revealed that the level of attitude of mobile assisted pedagogy approach in teaching science of prospective teachers is moderate in nature and there is a significant difference is exists based on the sub samples. Based on the result pedagogy approach of future teachers will be increased with the support of new mobile technology